So-Called Sovereign Settlers: Settler Conspirituality and Nativism in the Australian Anti-Vax Movement - Madi Day; Bronwyn Carlson (Humanities, 2023)
The COVID-19 pandemic, and the social and economic instability that followed, has given new life to conspirituality and far-right ideology in so-called Australia. This article discusses how politico-spiritual communities invested in both conspiracy theories and New Age spirituality have pieced together settler narratives about a New World Order and external threats to Western society from far-right and white supremacist Christian ideology circulated via new media. Using anti-colonial discourse analysis, we elucidate the undercurrent of white supremacist ideology in the Australian anti-vax movement, and highlight the misuse of Indigeneity in far-right and anti-vax narratives. We discuss how these narratives are settler-colonial and how conspiritualists co-opt and perform Indigeneity as a form of settler nativism. As a case study, we analyse the use of the term sovereignty by settlers attached to Muckadda Camp—a camp of ‘Original Sovereigns’ occupying the lawn outside Old Parliament house from December 2021 to February 2022. Using Indigenous critique from both new media and academia, we argue that although settlers may perform Indigeneity, they are exercising white supremacist settler narratives, and not Indigenous sovereignty.